Cancer mortality in the West Bank, Occupied Palestinian Territory. (December 2016) - Abu-Rmeileh, Niveen; Gianicolo, Emilio; Bruni, Antonella; Mitwali, Suzan; Portaluri, Maurizio; Bitar, Jawad; Hamad, Mutaem; Giacaman, Rita; Vigotti, Maria
Abstract Background The burden of cancer is difficult to study in the context of the occupied Palestinian territory because of the limited data available. This study aims to evaluate the quality of mortality data and to investigate cancer mortality patterns in the occupied Palestinian territory's West Bank governorates from 1999 to 2009. Methods Death certificates collected by the Palestinian Ministry of Health for Palestinians living in the West Bank were used. Direct and indirect age-standardised mortality rates were computed and used to compare different governorates according to total and specific cancer mortality. Furthermore, standardised proportional mortality ratios were calculated to compare mortality by urban, rural and camp locales. Results The most common cause of death out of all cancer types was lung cancer among males (22.8 %) and breast cancer among females (21.5 %) followed by prostate cancer for males (9.5 %) and by colon cancer for females (11.4 %). Regional variations in cancer-specific causes of death were observed. The central- West Bank governorates had the lowest mortality for most cancer types among men and women. Mortality for lung cancer was highest in the north among men (SMR 109.6; 95%CI 99.5-120.4). For prostate cancer, mortality was highest in the north (SMR 103.6; 95%CI 88.5-120.5) and in the south (SMR 118.6; 95%CI 98.9-141.0). Breast cancer mortality was highest in the south (SMR 119.3; 95%CI 103.9-136.2). Similar mortality rate patterns were found in urban, rural and camp locales. Conclusion The quality of the Palestinian mortality registry has improved over time. Results in the West Bank governorates present different mortality patterns. The differences might be explained by personal, contextual and environmental factors that need future in-depth investigations.